Pengembangan Model Mutasi dalam Upaya Peningkatan Kinerja - Falih Suaedi; Muhammad Nairil Anam; Windijarto Windijarto (Universitas Muhammadiyah Sidoarjo, 2017)
Mutation is one of the efforts of human resource management to place the right person in the right position to improve employee performance. Meanwhile, mutation is still problematic and has not been organized effectively since the models used are not entirely in accordance with rules and theoretical perspectives. Accordingly, an evaluation of the models used currently is required to implement the development of models of mutation to improve employee performance. This research generally aims to illustrate what kind of models of mutation is used and to develop models of mutation to improve performance of the Coordinating Body of Agricultural, Fisheries, and Forestry Extensions in Bangka-Belitung Islands Province. This research uses rules and theoretical perspectives and qualitative descriptive method. The research location is the offices of Regional Employment Board and Coordinating Body of Agricultural, Fisheries, and Forestry Extensions in Bangka-Belitung Islands Province. Informants of this research are people who are involved in making and receiving decisions of the mutations. The data collection is conducted with a preliminary observation, followed by field research that includes interviews and documentation. Data analysis techniques used in this research are qualitative data analysis techniques. From the research, it can be concluded that the development of models of mutation needs to be implemented to improve performance since the models used in 2015 were still insufficient, especially in the process of intensive and personal approach, which caused inaccuracy of data due to lack of good communication.